Screening of Musa germplasm for resistance and tolerance to nematodes - Speijer, P.R.; Waele, D. de; International Network for the Improvement of Banana and Plantain (1997)
In most regions of the world, nematodes are recognized as important pests of bananas. Because banana nematodes attack the root and/or corm tissues, plant growth and yield are affected. The objective of these technical guidelines is to stimulate interest in nematode resistance and tolerance screening in bananas, and to provide a methodology for carrying out such screening: plant material, nematode inoculum, screening experiments in pots or in the field, nematode reproduction assessment, and damage assessment INIBAP/CTA (French version available)